Resistance Lawyering - Farbman, Daniel S. (2019)
This is the story of a group of abolitionist lawyers who devoted themselves to working within a legal system that they considered to be fundamentally unjust and illegitimate. These “resistance lawyers” used the limited and unfriendly procedural tools of the hated Fugitive Slave Law of 1850 to frustrate, oppose, and, if possible, dismantle the operation of that law. Abolitionist resistance lawyers were forthrightly committed both to ensuring that their clients remained free and to using the cases that arose under the Fugitive Slave Law to wage a proxy war against the institution of slavery. Their daily direct service practices were inextricably linked to their movement politics and aspirations for systemic reform. Using new archival research that upends the existing historical consensus, I show that this linked practice was dramatically more effective than previously thought, both in protecting individual clients and as a means of building political opposition to slavery in local and national politics. This history should serve as a provocation for contemporary resistance lawyering. Many lawyers today practice within a legal system that they oppose in the hope of frustrating or dismantling that system. I suggest that today’s resistance lawyers can learn from the abolitionists’ integration of politics and daily practice as they fight to increase the political power and salience of their own work